2017
DOI: 10.5435/jaaos-d-15-00510
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acetabular Fractures in the Elderly

Abstract: The incidence of acetabular fractures in the elderly population is increasing. Fractures in this population differ from those in younger patients, with more frequent involvement of the anterior column, more comminution, and more severe articular impaction in elderly patients. Although acetabular fractures in geriatric patients are more likely the result of low-energy trauma, outcomes are generally poorer than those in young patients. Multiple management options have been proposed, but no intervention has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 42 publications
1
55
0
3
Order By: Relevance
“…The 47 patients that had survived until final follow up in the present study showed a fair functional outcome and no difference between operatively and non-operatively treated patients. While there seems to be consensus that good functional outcomes can be achieved by operative treatment of acetabular fractures in the elderly [12,[16][17][18], there is little data available on functional outcome after non-operative treatment. A recent retrospective case series of elderly patients with acetabular fractures that met criteria for surgery found that these patients can have good functional outcome also with non-operative treatment [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 47 patients that had survived until final follow up in the present study showed a fair functional outcome and no difference between operatively and non-operatively treated patients. While there seems to be consensus that good functional outcomes can be achieved by operative treatment of acetabular fractures in the elderly [12,[16][17][18], there is little data available on functional outcome after non-operative treatment. A recent retrospective case series of elderly patients with acetabular fractures that met criteria for surgery found that these patients can have good functional outcome also with non-operative treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary conversion rate to THA was 12.4% in the whole cohort and there was no significant difference between the operative and the non-operative group. Secondary conversion rates to THA have been reported to range from 10 to 37% [16] for patients in this age group when treated by open reduction and internal fixation and 15% when treated non-operatively [14]. A recent registry analysis of 678 acetabular fractures among all age groups reported that 19.8% of the patients required secondary THA [19].…”
Section: Discussionmentioning
confidence: 99%
“…A combined, multidisciplinary collaboration has been shown to reduce time to surgery, perioperative complications and mortality and overall improved outcomes in these patients. 18 The treatment aim is to shorten the period of immobilization, thereby minimizing adverse events associated with immobility, to restore pre-injury level of function and independence, to achieve pain relief and prevention of long-term pain, and to initiate osteoporotic treatment to prevent future fractures. In managing fragility fractures in our hospital, we adopted a multidisciplinary approach under a standardized protocol involving early co-management with physicians, anaesthetists and fracture liaison nurse.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 There is increasing interest in minimally invasive techniques due to reduced soft tissue disruption and reduced blood loss. 18 Computer-assisted fluoroscopy-navigated percutaneous screw fixation (minimally invasive) techniques, in particular, have been advocated for its accuracy and versatility in traumatic pelvic fractures. 16,17,[19][20][21] In a meta-analysis, computed tomography (CT)-guided navigation was associated with the lowest rate of screw malposition.…”
Section: Introductionmentioning
confidence: 99%
“…As the worldwide population ages and the elderly remain active later in life, the incidence of acetabular fractures among patients >60 years of age has increased by 2 to 3 times over the past 3 decades 1 - 3 . The anterior column-posterior hemitransverse fracture pattern, the classic acetabular fracture in the geriatric population, is often associated with protrusion of the femoral head and medial migration of the quadrilateral surface (QLS) 4 - 6 .…”
mentioning
confidence: 99%